Engineering properties of lightweight aggregate concrete containing limestone powder and high volume fly ash - Shafigh, Payam; Nomeli, M.A.; Alengaram, Ubagaram Johnson; Mahmud, Hilmi; Jumaat, Mohd Zamin (Elsevier, 2016)
Concrete industry is one of the major sources of consuming high volume of natural resources. On the other hand, cement industry is a significant point source of carbon dioxide emissions due to the decomposition of raw material and burning fuel during the manufacturing process. As the demand for concrete is growing, one of the effective way to minimize the negative environmental impact of the industry is the use of waste and by-product materials as cement and aggregate replacement in concrete.